Proceedings of the 16th International Conference on Enterprise Information Systems 2014
DOI: 10.5220/0004973604960501
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Disclosure - From the Accounting to the Report Perspective

Abstract: Abstract:This paper focus on the environmental disclosure (ED) promoted by firms, due to the strong demand for information and identification of the relevant data that pursuit the new legal requirements. The methodology is separate, by one side, on the theoretical framework based on the disclosure of environmental information (EI) and the true and fair view based on the accounting perspective. Indeed, the paper provides an understanding of the Patten (2002)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Carreira conducts a research that takes a sample of 24 firms listed on the Lisbon Euronext Stock Market. Carreira et al (2014) conclude that firm size and profitability significantly influence the ED but do not affect on the economic sector. A research in Italy and the US by Boesso and Kumar (2007) on ED quality concluded that business complexity, volatility, award, and intangible asset significantly affect the volume of voluntary disclosure in Italy.…”
Section: Environmental Disclosurementioning
confidence: 77%
“…Carreira conducts a research that takes a sample of 24 firms listed on the Lisbon Euronext Stock Market. Carreira et al (2014) conclude that firm size and profitability significantly influence the ED but do not affect on the economic sector. A research in Italy and the US by Boesso and Kumar (2007) on ED quality concluded that business complexity, volatility, award, and intangible asset significantly affect the volume of voluntary disclosure in Italy.…”
Section: Environmental Disclosurementioning
confidence: 77%
“…Another case with research conducted by Elshabasy (2017), Abubakar (2017) as well as Lu & Abeysekera (2014) which do not find the effect between leverage on environmental disclosure. Company size has a positive effect on environmental disclosure as evidenced by Ijma & Yusnita (2018), Burgwal & Vieira (2014) as well as Carreira et al(2014) found that environmental disclosure was not influenced by company size. This study has a purpose in order to know and provide empirical evidence related to the effect of profitability, leverage, and company size on environmental disclosure and the role of independent commissioners in moderating the relationship.…”
Section: Introductionmentioning
confidence: 96%
“…The awareness on the importance of environmental related information disclosure in the business community has increased. Corporate annual reports and other stand-alone reports have been used as main medium of communication with stakeholders [2].…”
Section: Introductionmentioning
confidence: 99%